2015
DOI: 10.1177/0192623314564254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Periodic Acid-Schiff-Positive Granular Deposits in the Hippocampus of SJL/J Mice

Abstract: Periodic acid-Schiff (PAS)-positive granular deposits in the hippocampus have been reported previously in certain inbred mouse strains such as C57BL/6 and the senescent-accelerated mouse prone-8. Here, we report for the first time that similar PAS-positive granules age dependently occur in SJL/J mice, a mouse strain, for instance, used for central nervous system disease research. Moreover, similar granules stained intensely positive with a polyclonal antibody directed against p75 neurotrophin receptor (p75 NTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The neutral histology techniques confirmed PAS-positive argyrophilic granules in the hippocampus of infected ApoE −/− mice, and their distribution resembled previous observations [ 1 3 , 27 , 28 ]. The immunohistochemistry results with the anti-peptidoglycan antibody indicated an enhanced occurrence of age-related granules in infected brains, together with diffuse areas of immunoreactivity when compared with sham-infected mice.…”
Section: Discussionsupporting
confidence: 88%
“…The neutral histology techniques confirmed PAS-positive argyrophilic granules in the hippocampus of infected ApoE −/− mice, and their distribution resembled previous observations [ 1 3 , 27 , 28 ]. The immunohistochemistry results with the anti-peptidoglycan antibody indicated an enhanced occurrence of age-related granules in infected brains, together with diffuse areas of immunoreactivity when compared with sham-infected mice.…”
Section: Discussionsupporting
confidence: 88%
“…10,34,57,59 PAS stains of aging mouse brain have shown common PASpositive granules in the hippocampus and other regions of many mouse strains. 13,26,32,35,57 We confirmed its common occurrence in a few strains. Focal thalamic mineralization, the frequency of which was strain-related, was found to be blood vessel associated and highest in C3H mice.…”
Section: Discussionsupporting
confidence: 76%
“…We performed PAS staining on 9 mice from representative strains (FVB/NJ, C57BL/6J, PWD/PhJ, BUB/BnJ, CBA2/J) and confirmed that the mice had PAS-positive granules in the neuropil of the hippocampus of all strains reviewed. 13,26,32,35,57 Many neurons in the cerebral cortex, cerebellum (Purkinje cells), medulla, thalamus, and spinal cord often had small PAS+ granules which usually were not present as pigmented granules in H&E stain nor autofluorescence with a GFP green filter. The cerebellar Purkinje cells had pigmented cytoplasm occasionally but were also usually not autofluorescent.…”
Section: Hirano-like Bodies and Other Lesionsmentioning
confidence: 99%
“…Each mouse brain section was carefully mounted on the glass slide and was stained with periodic acid-Schiff (PAS). The pathological granular structures in different regions of interest (ROI), i.e., the hippocampus, prefrontal cortex and entorhinal cortexes of the mouse brains were stained positively with periodic acid-Schiff (PAS) [ 70 , 71 ]. The granules were observed to be round to ovoid in appearance, when observed under light microscope using scale bars 50 µm.…”
Section: Methodsmentioning
confidence: 99%